The lizard of oz - Stine, R. L. (Stine, R. L. Goosebumps most wanted, 2016)
Kate Orton loves animals, especially unusual ones. So when she sees a pop-up ad on her computer for an amazing lizard from Australia, she has to have it. The ad says the lizard is actually a kind of chameleon--it can change its color to blend in with its surroundings. But what makes this lizard really strange is that it's a copycat--the ad says it can even change its shape. Kate's parents don't believe all the claims in the ad, but they tell her to go ahead and order it. They tell her not to be disappointed if it's just a plain old lizard. After anxiously checking the mail every day for two weeks, the package finally arrives. But when she finally opens it--there's no lizard inside. There's only an egg with a written warning. Is Katie ready for what's about to hatch?